2011
DOI: 10.1002/hep.24678
|View full text |Cite
|
Sign up to set email alerts
|

IL28B alleles associated with poor hepatitis C virus (HCV) clearance protect against inflammation and fibrosis in patients infected with non-1 HCV genotypes

Abstract: on behalf of the Swiss Hepatitis C Cohort Study Group the ANRS HC EP 26 Genoscan Study GroupGenetic polymorphisms near IL28B are associated with spontaneous and treatmentinduced clearance of hepatitis C virus (HCV), two processes that require the appropriate activation of the host immune responses. Intrahepatic inflammation is believed to mirror such activation, but its relationship with IL28B polymorphisms has yet to be fully appreciated. We analyzed the association of IL28B polymorphisms with histological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
134
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(154 citation statements)
references
References 48 publications
17
134
3
Order By: Relevance
“…The median fibrosis progression rate of 0.07 per year observed in this cohort was similar to or lower than reported in other studies of patients with chronic HCV-infection [16][17][18][19][20], but the progression rate was higher than in studies of young females who contracted an HCVinfection accidentally as a result of infected anti-D immunoglobulin in Ireland and Germany [5,21]. In a meta-analysis of the stage-specific fibrosis progression rate in different populations of HCV-patients, the mean progression rate among the IDUs were: F0-F1 0.116, F1-F2 0.085, F2-F3 0.085 and F3-F4 0.130 [20].…”
Section: Discussionsupporting
confidence: 86%
“…The median fibrosis progression rate of 0.07 per year observed in this cohort was similar to or lower than reported in other studies of patients with chronic HCV-infection [16][17][18][19][20], but the progression rate was higher than in studies of young females who contracted an HCVinfection accidentally as a result of infected anti-D immunoglobulin in Ireland and Germany [5,21]. In a meta-analysis of the stage-specific fibrosis progression rate in different populations of HCV-patients, the mean progression rate among the IDUs were: F0-F1 0.116, F1-F2 0.085, F2-F3 0.085 and F3-F4 0.130 [20].…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, in contrast to the core region, consensus has not been reached as to the relationship between disease progression and the IL28B SNP, which is associated with IFN resistance (14)(15)(16)(17). Previously, we reported that there was no correlation between the onset of HCC and the IL28B SNP (9).…”
Section: H Epatitis C Virus (Hcv)-related Liver Disease Gradually Advmentioning
confidence: 97%
“…The role of these SNPs in the host inflammatory response and evolution of chronic infection in untreated chronic HCV patients is not well understood. Recent studies yielded contradictory results and have shown rs12979860 CC (or rs8099917 TT) association with more advanced fibrosis or cirrhosis [16] [17] and worse clinical outcomes [18], while others have reported rs12979860 TT (or rs8099917 GG) to be associated with more advanced fibrosis or cirrhosis [19] IL28B genotype with fibrosis [22]. The aim of our study was to determine whether SNPs rs12979860 and rs8099917 can be considered a prognostic host factor in untreated chronically HCV-infected patients from an Argentine cohort, by analyzing host haplotypes involved in modulation of patient's immune responses.…”
Section: Introductionmentioning
confidence: 99%